ERGONOMIC ANALYSIS OF CHECKOUT OPERATORS WORKSTATION (Fiep Bulletin - online, 2017)
The purpose of this study was to develop an ergonomic analysis at checkout operators' workspace, located inCuritiba, Paraná. Periodic visits were made to the establishment, with application of questionnaires to employees, analyzes ofnoise and furniture. Environmental conditions observed showed the deficiency in the physical arrangement and organization ofthe workspace in addition, the workplace does not provide comfort for workers in their jobs. From the questionnaire, the operatorsprofile were obtained and was possible to quantify the main operators' complaints, in which prevailed the associated furniture.With the results of this study was drawn up an ergonomic prototype of the workspace, to meet Appendix I of the regulation NR17,ensuring the conditions of service and comfort, in addition to the health and safety of users.
Keywords: Ergonomic analysis; Occupational noise; Checkout operators